2021
DOI: 10.1097/scs.0000000000007668
|View full text |Cite
|
Sign up to set email alerts
|

Safe Zone for Dissection in Frontotemporal Region to Avoid Injury to the Temporal Branch of Facial Nerve

Abstract: The objective of this study is to provide a reliable roadmap for temporal branch of the facial nerve, in order to minimize, the risk of injury to the nerve during surgical dissections. A literature search was conducted on temporal branch of facial nerve. The date search range was 1950 to 2017. Databases searched included Medline, Web of science, Biosis, SciELO, Data Citation, and Zoologic Records. Data were collected on, author specialty, date of publication, and the relationship of the temporal branch of faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…17 In the temporal region, the fascia layer that the TBFN lies on has been controversial, 2,6,12,[16][17][18] compared with the intuitive results from previous studies about the course of the TBFN. [19][20][21][22] Using layer-by-layer dissection, Agarwal et al described a fascial transition zone in the frontotemporal region that the TBFN crossed from the subsuperficial temporal fascia to run within the superficial temporal fascia. 6 The present study histologically confirmed that the TBFN fibers were consistently identified in the subsuperficial temporal fascia, which differs dramatically on the two sides of the ITS.…”
Section: Discussionmentioning
confidence: 99%
“…17 In the temporal region, the fascia layer that the TBFN lies on has been controversial, 2,6,12,[16][17][18] compared with the intuitive results from previous studies about the course of the TBFN. [19][20][21][22] Using layer-by-layer dissection, Agarwal et al described a fascial transition zone in the frontotemporal region that the TBFN crossed from the subsuperficial temporal fascia to run within the superficial temporal fascia. 6 The present study histologically confirmed that the TBFN fibers were consistently identified in the subsuperficial temporal fascia, which differs dramatically on the two sides of the ITS.…”
Section: Discussionmentioning
confidence: 99%
“…The frontotemporal branch of the facial nerve (referred to for the remainder of this article as the frontotemporal nerve), which innervates the frontalis, corrugator supercilii, and procerus muscles, is 1 of the 5 motor branches of the facial nerve. There are many studies on its facial course and danger zones for injury 6–10 . The primary aim of these studies was to describe how to avoid frontotemporal nerve injury during various surgical procedures; however, in cases of trauma injury may be inevitable.…”
mentioning
confidence: 99%
“…There are many studies on its facial course and danger zones for injury. [6][7][8][9][10] The primary aim of these studies was to describe how to avoid frontotemporal nerve injury during various surgical procedures; however, in cases of trauma injury may be inevitable. In the case of injury, the first-line treatment is tension-free primary neurorrhaphy.…”
mentioning
confidence: 99%